(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study investigated the effect of schools supervision on the academic performance of Basic science students in Ahoada East Local Government Area of Rivers State, Nigeria. Six research questions and six hypotheses were raised to guide this study. A descriptive survey design was adoptedfor the study with a study population of two hundred (200) junior secondary school students, and one hundred and seventy five (175) junior secondary schools was used for the study through a multi-stage sampling technique which was adopted to select three hundred and seventy – five (375) participants. Structured questionnaires were used for data collection and all were analyzed, using simple percentage and chi- square statistical tool to test the hypotheses at 0.05 level of significance. The result of the study revealed the level of effect school supervision has on the academic performance of secondary school students on Basic science which was 76.9% indicating that more than half of the total respondents as opposed to less than 40% of the respondents that indicated 24.1% and based on that, it was concluded that the rate of school supervision is directly proportional to the academic performance of secondary school students on Basic science as a hallmark for educational improvement. It was recommended that government should increase effort on finding school supervision as to improve the quality of education which are of great significance toward students’ academic performance.